Analysis of Heterogeneous Settlement of Connecting Sections of Embankment on Deep Soft Ground Based on PLAXIS. Issue 6 (April 2020) - Tang, Mingli; Sha, Yonghua; Chai, Yucheng; Zhang, Yidi
Abstract: The article analyzes the uneven settlement of the dam gate connection section of a reclamation project along the coast of eastern Zhejiang by PLAXIS finite element software, and compares and analyzes the in-situ monitoring results to understand the settlement development law of the dam gate connection section during operation and the location of the largest uneven settlement. Through analysis, after the sluice and the seawall are connected, the sluice settlement in the first year of the operation period is 5.51 mm, the settlement at the seawall is 105.30 mm, and the settlement difference is 99.79 mm; the cumulative settlement of the sluice is 9.01 mm, and the cumulative settlement at the seawall is 214.00 mm and the settlement difference is 204.99 mm. The uneven settlement of the connecting section of the dyke is mainly manifested at the junction of the empty box of the sluice and the riprap area of the seawall. When the uneven settlement is large, it will cause road cracks.